Dubbing in Poland, Russia, and Bulgaria as an object of media discourse: a comparative analysis - Kulas, Karolina (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The study of dubbing in the media discourse in Poland, Russia, and Bulgaria, which was the subject of this research, was aimed at indicating the position and prospects of its development in countries where the voice-over technique prevails. The research material consisted of online articles, publications of film translation researchers, and posts on forums devoted to interlingual dubbing. The analysis of the texts showed that dubbing in the analyzed countries has a similar range of impact: it mainly relates to the translation of animated productions. In addition to a number of advantages of dubbing, a number of disadvantages were observed, which do not help strengthen its position in the studied countries. These include limiting access to the original version, the possibility of manipulating the audience, the cost-intensive translation process These limitations lead to the conclusion that dubbing will not dominate the audio-visual translation market in these countries in the near future.